APLIKASI PERANCANGAN PROGRAM PENJUALAN TOPI SECARA KREDIT (Studi kasus: Gudang Topi Cikampek Jawa Barat) - Suharyanti, Nining; Murniyati, Murniyati (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to design a Accounting Information System for Credit TOPI Sales that has not been computerized in the Karawang regency cap warehouse, to be computerized. Hat warehouse is a business that sells hat, which handles cash and credit sales. But the sales recording system still uses the recording in the ledger. The method used is interviews and observations, this research was conducted at the hat warehouse, which is located in Wncimekar, Kota Baru, Karawang District of Karawang. The results of research on the design of Accounting Information Systems for Sales of Hats on Credit, which can help in the process of selling hats. to be more effective and efficient in the process. So far, the company uses a manual system by recording all data and transactions in one book, so that it can cause data loss. With the proposed system of accounting information system design, the sale of hats on credit is expected to help companies manage data and transactions. The results to be achieved are the Accounting Information System for Credit Sales Hats consisting of, Data Collection System on Data of Goods, Data on Credit Packages, Customer Data, Credit Sales Transactions, Installment Transactions and Reports.